Immunoproteomics reveal increased serum IgG3/5 binding to Dermatophagoides and yeast protein antigens in severe equine asthma in a preliminary study - Schnabel, Christiane L.; Jentsch, Maria-Christin; Lübke, Sabrina; Kaiser-Thom, Sarah; Gerber, Vinzenz; Vrtala, Susanne; Huang, Huey-Jy; Rhyner, Claudio; Wagner, Bettina; Hoffmann, Ralf; Volke, Daniela (Frontiers in Immunology, 2023)
Severe equine asthma (SEA) is a common, chronic respiratory disease of horses characterized by hyperreactivity to hay dust which has many similarities to severe neutrophilic asthma in humans. SEA provoking antigens have not been comprehensively characterized, but molds and mites have been suggested as relevant sources. Here, we identified relevant antigen candidates using immunoproteomics with IgG isotype binding analyses. Proteins from Dermatophagoides pteronyssinus (Der p) were separated by two-dimensional gel electrophoresis followed by immunoblotting (2D immunoblots) resulting in a characteristic pattern of 440 spots. After serum incubation, antibody (Ig)-binding of all Ig (Pan-Ig) and IgG isotypes (type-2-associated IgG3/5, type-1-associated IgG4/7) was quantified per each spot and compared between asthmatic and healthy horses’ sera (n=5 per group). Ig binding differences were detected on 30 spots. Pan-Ig binding was higher with asthmatics’ compared to healthy horses’ sera on four spots, and IgG3/5 binding was higher on 18 spots. Small IgG4/7 binding differences were detected on 10 spots with higher binding with asthmatics’ sera on four, but higher binding with healthy horses’ sera on six spots. Proteins from the spots with group differences were identified by liquid chromatography mass spectrometry including mite and yeast proteins. The latter likely originated from the feeding substrate of the Der p culture. Prioritized antigen candidates amongst the proteins identified were Der p 1, Der p 11, group 15 allergens, myosin heavy chain, and uncharacterized Der p proteins. Additionally, yeast enolases, alcohol dehydrogenase (ADH), phosphoglycerate kinase (PGK), glyceraldehyde-3-phosphate dehydrogenase, and heat shock proteins were prioritized. Eleven antigen candidates were tested for confirmation by ELISAs using the respective proteins separately. Differences of asthmatics’ vs. healthy horses’ serum Ig binding to Der p 1, Der p 18 and three yeast enzymes (enolase, ADH, PGK) confirmed these as promising antigens of immune responses in SEA. Antigens with relevance in SEA were newly identified by immunoproteomics, and yeast antigens were considered for SEA for the first time. Serum IgG3/5 binding to relevant antigens was increased in SEA and is a novel feature that points to increased type-2 responses in SEA, but requires confirmation of the corresponding cellular responses.